Exploring the Enhancement of Educational Systems through Information and Communication Technology: An Investigative Study - Tamanna Quraishi; Nargis Hakimi; Musawer Hakimi; Maleena Safi; Fazila Akrami; Mursal Akrami; Khatera Akrami; Zahra Nejrabi (Journal of Social and Humanities, 2024)
This study investigates the integration of Information and Communication Technology (ICT) in educational systems, aiming to analyze its current state, evaluate its impact on teaching and learning, explore its role in accessibility, and recommend optimal integration strategies. A structured questionnaire was designed and distributed online to gather data from 140 participants, including lecturers and students across various faculties. The questionnaire captured demographic information, perceptions of ICT integration effectiveness, challenges faced, and its impact on teaching methods and student learning outcomes. Data analysis revealed a generally positive outlook on ICT integration effectiveness, with a significant proportion of respondents perceiving it as moderately to extremely effective. Challenges faced in integrating ICT varied among respondents, with a mixed perception ranging from moderate to high levels. However, respondents acknowledged the positive impact of ICT on teaching methods and student learning outcomes, highlighting its potential to enhance educational experiences. Furthermore, the study found that ICT initiatives contribute significantly to promoting inclusivity in education, emphasizing the importance of considering diverse stakeholder perspectives. Based on the findings, actionable recommendations were proposed for optimizing ICT integration to improve educational quality. Overall, the study provides valuable insights into the current state of ICT integration in educational systems and offers practical implications for educators, policymakers, and stakeholders.